PERAN EVENT PARIWISATA BUDAYA DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT KOTA SINGKAWANG: STUDI LITERATUR - Dyah Andrianti (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2026)
Cultural tourism is one of the sectors that plays an important role in regional economic development. The organization of various cultural events not only serves as a means of preserving cultural heritage but also acts as an effective instrument for attracting tourists and stimulating local economic activities. Singkawang City, as one of the leading tourist destinations in West Kalimantan Province, possesses rich cultural diversity and is widely recognized for its cultural events, particularly the Cap Go Meh Festival, which has become part of Indonesia’s national tourism agenda. This study aims to analyze the role of cultural tourism events in improving the economic conditions of the people of Singkawang City. The research employs a literature review method by examining various scholarly articles, books, government reports, statistical documents, and other relevant academic sources. The findings indicate that cultural tourism events play a strategic role in increasing tourist arrivals, promoting the growth of micro, small, and medium enterprises (MSMEs), creating employment opportunities, enhancing community income, and strengthening regional cultural identity. In addition to generating direct economic impacts through increased transactions of goods and services, cultural events also produce indirect economic benefits, including destination promotion and increased investment in the tourism sector. Therefore, the development of cultural tourism events should be continuously supported through collaboration among local governments, business actors, cultural communities, and local residents in order to foster inclusive and sustainable economic development.